2018
DOI: 10.1002/solr.201700221
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Fabrication Gettering and Hydrogenation Treatments for Silicon Heterojunction Solar Cells: A Possible Path to >700 mV Open‐Circuit Voltages Using Low‐Lifetime Commercial‐Grade p‐Type Czochralski Silicon

Abstract: Pre-fabrication gettering and bulk hydrogenation processes are applied to lowbulk-lifetime (25 μs) p-type Czochralski silicon wafers before silicon heterojunction (SHJ) solar cell fabrication, resulting in effective minority carrier lifetime enhancements by a factor of six. On complete SHJ solar cells, this translates to an improvement in the open-circuit voltage (V OC ) of 71 mV, resulting in V OC values as high as 692 mV. This remarkably high V OC suggests that efficiencies approaching 25% could be possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 22 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…The difference in forming gas and pure nitrogen is the 10% hydrogen in this experiment. Hydrogenation is a very well‐developed method to passivate defects in c‐Si solar cells and widely used for curing the light and elevated temperature–induced degradation in c‐Si solar cells . Because water molecules contain hydrogen atoms and the humidity in the laboratory was about 55%, we speculate that the increment in the iV oc after the annealing in the air could have resulted from the moisture in the air.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The difference in forming gas and pure nitrogen is the 10% hydrogen in this experiment. Hydrogenation is a very well‐developed method to passivate defects in c‐Si solar cells and widely used for curing the light and elevated temperature–induced degradation in c‐Si solar cells . Because water molecules contain hydrogen atoms and the humidity in the laboratory was about 55%, we speculate that the increment in the iV oc after the annealing in the air could have resulted from the moisture in the air.…”
Section: Resultsmentioning
confidence: 96%
“…After the 820 °C annealing, the TOPCon structure provides significant passivation with the iV oc of 705 mV and the J 0 of 14.9 fA cm −2 at the minority carrier density (MCD) of 1 × 10 15 cm −3 . A few things happen during the annealing: 1) the a‐Si:H is crystallized into poly‐Si as proven by UV‐Raman measurements, 2) the P atoms are activated into dopants as measured by electrochemical voltage (ECV) measurements to provide free carriers and the field‐effect passivation, 3) Si‐H bonds are broken and H diffuses out or diffuses into the c‐Si, 4) the SiO x restructures and pin‐holes could form, and 5) P diffuses through the SiO x into the c‐Si as measured by ECV measurement as well . All of these could affect the passivation quality, but we found the improved field‐effect passivation as the dominating factor to determine the passivation quality, because a undoped poly‐Si made from an intrinsic a‐Si:H precursor itself shows a much lower passivation improvement than with the n‐poly‐Si from a P‐doped a‐Si:H precursor .…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that with the addition of a dedicated gettering step to improve material quality, Descoeudres et al observed an efficiency gain of %0.2% abs in batches of p-type SHJ solar cells. [10] In previous studies, we have also demonstrated the role of gettering in increasing the lifetime of p-type Cz silicon, [5,11,12] which translated to a %1% abs increase in the efficiency of SHJ solar cells. These results together indicate the need for gettering as a defect-engineering process to enhance the quality of p-type silicon wafers for SHJ solar cells applications.…”
mentioning
confidence: 80%
“…[3] Thus, silicon wafers used for SHJ solar cells do not benefit from the gettering of metallic impurities and hydrogenation of bulk defects that are naturally incorporated in the fabrication sequence of aluminum back surface field (Al-BSF) and passivated emitter and rear cell (PERC) solar cells. [4,5] Therefore, highquality n-type Czochralski (Cz) silicon with bulk lifetimes (τ bulk ) > 1 ms is required in the fabrication of SHJ solar cells. [6,7] Although there have been cost reductions on n-type Cz silicon over the last 10 years, p-type Cz silicon is still 8% cheaper than n-type Cz (at a thickness of 180 μm).…”
mentioning
confidence: 99%
“…A similar approach has been developed in Ref. [14], with gettering and hydrogenation of the wafer through SiN x layer and rapid thermal firing. We investigate the passivation quality of double-side textured wafers treated with HTO for variable treatment time by passivating the c-Si surfaces with a-Si:H layers growth via plasma enhanced chemical vapor deposition (PECVD).…”
Section: Introductionmentioning
confidence: 99%